Calderón en su laboratorio: la evidencia de atajos comentados y repartos - Greer, Margaret R. (Anuario Calderoniano, 2015)
Este ensayo se dedica al tratamiento editorial de los pasajes atajados, con o sin breves comentarios y enmiendas marginales, en los manuscritos autógrafos y parcialmente autógrafos de Calderón de la Barca. Considerando las notas marginales a la luz de la caligrafía de Calderón y el color de la tinta empleada, se analiza hasta qué punto es posible determinar qué cortes habría sugerido, rechazado o aceptado el dramaturgo, y se discute el tratamiento de ellos por ciertos editores. En adición, se consideran los indicios que podemos derivar de la caligrafía en los repartos de algunos manuscritos calderonianos. «Calderón in his Lab: The Evidence of Cast Lists and Comments by Text Marked for Cutting» This essay is devoted to the editorial treatment of passages marked for possible omission, with or without brief marginal notes and suggested alterations, in autograph and partially autograph manuscripts of Calderón de la Barca. Comparing the calligraphy of the notes and the ink color employed in marking the passages with Calderón’s handwriting in the text of the manuscript, I investigate to what degree it is possible to determine which cuts the playwright might have suggested, accepted, or rejected, and the treatment of such passages by certain editors. I also consider certain evidence we can derive from the handwriting in the cast lists of some calderonian manuscripts. PALABRAS CLAVE / KEYWORDS: Calderón de la Barca; manuscritos autógrafos; caligrafía; política editorial; repartos / Calderón de la Barca; autograph manuscripts; calligraphy; editorial policy; cast lists.